The Optimised Statistical Model for Enzymatic Hydrolysis of Tapioca by Glucoamylase Immobilised on Mesostructured Cellular Foam Silica - Joni Agustian; Lilis Hermida (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Enzymatic hydrolysis of starches using free glucoamylase to reducing sugars have difficulties in recovering and recycling of the enzyme, hence immobilisation on inert supports were widely studied. However, effectiveness of the immobilised glucoamylase were merely observed only on soluble starches. It was considered a valuable thing to know performance of glucoamylase on Mesostructured Cellular Foam (MCF) silica in hydrolysing of tapioca. An optimised study on enzymatic hydrolysis of tapioca using glucoamylase on MCF silica (9.2T-3D) and its kinetics were described including justification of the predicted model as it was required to develop in large scale operations. Central Composite Design was used to model the process by studying effects of three factors on DE values after enzyme immobilisation.  Immobilisation of glucoamylase on this support gave up to 82% efficiency with the specific activity of 1,856.78 U.g-1. Its used to hydrolysis of tapioca resulted DE values of 1.740-76.303% (w/w) where the highest DE was obtained at pH of 4.1, temperature of 70 ℃ and agitation speed of 140 rpm. The optimisation produced a polynomial quadratic model having insignificant lack-of-fit and low standard deviation, so that it was applicable and reliable in simulating the DE with only 0.80% of data were not described. Temperature affected the process highly, but the buffer pH, agitation speed and factorial interactions were considered not important. KM value for immobilised enzyme was better than the free glucoamylase, however, its reaction rate was slower than the free glucoamylase catalysis. Copyright © 2019 BCREC Group. All rights reserved